Social status Roman Tripolitaniaan and Nigeria (2015)
Modern authors have persistently made incisive efforts to interpret social status and other social cultural aspects o f the society in antiquity and modern times. This paper sets out to interpret social status in Roman Tripolitania and Nigeria. For Roman Tripolitania, it utilizes Latin inscriptions while drawing distinctions between status o f the high and low. In Nigeria obituaries on daily newspapers are examined in an attempt to explain that, more often than not, the high and mighty memorialized their departed on the pages ofnewspapers. This paper contends that in Roman Tripolitania and Nigeria, erecting epitaphs and displaying obituaries were intentional; to memorialize the dead, to flaunt the status of personalities, to enumerate their achievements, to demonstrate heirship and possibly, to attract the interest o f the powers that be. The study adopts a methodology that is both historical and comparative to highlight issues that border on social status in both societies. The data accessed were subjected to content analysis. Further studies that may examine burial customs and ceremonies in ancient Rome and modern Nigeria are recommended.